Pursed Lip Breathing Exercises and Diaphragmatic Breathing Exercises in Increasing Forced Vital Capacity and First Second Expiratory Volume (VEF1) in Post Covid-19 Patients - Muhammad Henrie Irawan; Yuly Persitiowati; Agustin Agustin (Indonesian Journal of Global Health Research, 2024)
Healthcare workers have a significant risk of being infected with COVID-19, as well as the risk of experiencing Post-COVID Syndrome symptoms, with fatigue being the most commonly reported. Reality shows that after being declared recovered from COVID-19, patients do not immediately become free from complaints such as shortness of breath, fatigue, pain, or depression. Post-COVID-19 sequelae symptoms cannot be ignored, as they can interfere with daily activities and reduce the quality of life for COVID-19 survivors. This study aims to analyze the comparison of Pursed Lip Breathing exercises and Diaphragm Breathing exercises in increasing forced vital capacity (FVC) and first second expiratory volume (VEP1) in post-covid-19 patients at Aji Muhammmad Parikesit Tenggarong Hospital. This research is a quantitative study that was carried out using post-covid patient data, with a sample of 18 respondents to the Pursed Lip Breathing exercise and 18 respondents to the Diaphragm Breathing exercise. The results showed that the results of the two different tests on average showed that there were significant differences before and after treatment in increasing forced vital capacity (FVC) and first second expiratory volume (VEF1) with Pursed Lip Breathing in post-covid-19 patients at Aji Hospital Muhammmad Parikesit Tenggarong and the results of the two different tests on average showed that there were significant differences before and after treatment in increasing forced vital capacity (FVC) and first second expiratory volume (VEF1) with Diaphragm Breathing in post-covid-19 patients at Aji Muhammad Parikesit Tenggarong Hospital.